Slag-resistant wear-resistant castable and preparation method thereof
By optimizing the assembly ratio and modification treatment of the casting materials, the problems of insufficient compressive, impact, wear resistance and thermal shock resistance under high temperature conditions are solved, and the effect of significantly improving the compressive flexural strength and high temperature resistance is achieved.
Patent Information
- Application Number
- CN202411656386.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
AI Technical Summary
The existing castable materials have insufficient impact resistance, compression resistance, wear resistance and thermal shock resistance under high temperature conditions, and the strength of the hydrate is reduced after dehydration at high temperatures.
By optimizing the composition distribution ratio, it includes the use of 50-65% corundum aggregate, 8-12% mullite, 5-6% silicon carbide, 6-8% modified calcium oxide, 1-8% zirconia, 2-3% alumina, 4-6% calcium aluminate cement and 1-2% water reducer, and the modification treatment of modified calcium oxide and zirconia was used to coat and polymerize with silane coupling agent to enhance the high temperature and corrosion resistance of the material.
It significantly improves compressive flexural strength, reduces porosity, enhances the material's high temperature resistance and toughness, and improves impact, wear and thermal shock stability.
Smart Images

Figure BDA0005142209800000071 
Figure BDA0005142209800000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of castables, in particular to a slag-resistant and wear-resistant castable and a preparation method thereof. Background Art
[0002] The parts of thermal equipment such as blast furnaces, hot blast stoves, circulating fluidized beds, waste incinerators, catalytic cracking units, etc. that are prone to wear, penetration and erosion are key parts of high-temperature equipment. They are usually cast from amorphous refractory materials. The refractory castable is a non-adhesive mixture composed of aggregates, fine powders and binders. The aggregates and fine powders are usually composed of corundum and mullite, and the binder is usually calcium aluminate cement.
[0003] Patent 202311387846.0 discloses a wear-resistant castable for high-temperature wear parts of the lining of a thermal kiln and a preparation method thereof. It uses raw materials such as fused zirconium corundum, silicon carbide, alumina powder, zirconium oxide, pure calcium aluminate cement, antioxidants, and inorganic binders, and introduces zirconium oxide with a high melting point and low expansion coefficient to enhance the wear resistance and thermal shock stability of the castable. However, a large amount of pure calcium aluminate cement is introduced into this scheme, accounting for 5-12% of the weight. Although the strength is enhanced in a short time (6-24h), its strength will be severely reduced after the hydrate is dehydrated at medium and high temperatures in the later stage.
[0004] Patent 202110036184.7 discloses a flow stabilizer castable for a long-life tundish, a flow stabilizer and a preparation method thereof. Brown corundum, white corundum, α-Al2O3 powder, fused magnesia spinel, sintered magnesia spinel powder, zirconia powder, cement, stainless steel fiber, explosion-proof agent, water reducer, retarder and other raw materials are used to prepare an amorphous castable by mixing and stirring. Due to the introduction of stainless steel fiber, the later compressive strength and mechanical impact resistance of the castable are enhanced. However, the thermal expansion coefficient of stainless steel fiber at high temperature is large, which can easily cause different local stresses in the castable. At the same time, the chemical properties of stainless steel fiber are relatively active and easy to react with acidic gases in the flue, which seriously affects the stability of the structure during long-term operation.
[0005] How to reduce the impact of cement on refractory materials at high temperatures by adjusting the components, and continue to improve its initial bonding strength, later anti-erosion and erosion performance, compression resistance, wear resistance and thermal shock stability is a difficult point in the research and development of this industry. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a slag-resistant wear-resistant castable and a preparation method thereof to solve the problems of low impact resistance, compression resistance and wear resistance of the existing castable materials.
[0007] The purpose of the present invention is achieved by the following technical scheme: a slag-resistant and wear-resistant castable, which comprises the following components by weight: 50-65 parts of corundum aggregate, 8-12 parts of andalusite, 5-6 parts of silicon carbide, 6-8 parts of modified calcium oxide, 1-8 parts of zirconium oxide, 2-3 parts of aluminum oxide, 4-6 parts of calcium aluminate cement, and 1-2 parts of a water reducer.
[0008] Preferably, the corundum aggregate includes 10-15 parts of a particle size of 0-1mm, 35-40 parts of a particle size of 1-3mm, and 10-15 parts of a particle size of 3-5mm, and the andalusite particle size is 0-1mm.
[0009] Preferably, the alumina includes 1-2 parts of 0-5 μm particles and 1-2 parts of 1-2 cm short fibers.
[0010] Preferably, the modified calcium oxide is prepared according to the following method:
[0011] S1. dissolving a silane coupling modifier in an organic solvent;
[0012] S2. The calcium oxide powder is put into an organic solvent and stirred for 30 minutes;
[0013] S3. Filter, wash and dry the suspension.
[0014] Preferably, the zirconium oxide is modified zirconium oxide.
[0015] Preferably, the modified zirconium oxide is prepared according to the following method:
[0016] S1. dissolving a silane coupling modifier in an organic solvent;
[0017] S2. The zirconium oxide powder was added to the organic solvent and stirred for 30 min;
[0018] S3. Filter, wash and dry the suspension.
[0019] Preferably, the water reducing agent is one or more of sodium tripolyphosphate, sodium hexametaphosphate, and sulfonated naphthalene formaldehyde polymer.
[0020] Preferably, the silane coupling modifier is one of a mercaptosilane coupling modifier, an aminosilane coupling agent, and a vinylsilane coupling agent.
[0021] The present invention also aims to provide a method for preparing a slag-resistant and wear-resistant castable, which comprises weighing each component according to a proportion and mixing and stirring each component.
[0022] Preferably, the zirconium oxide is modified zirconium oxide, and the slag-resistant wear-resistant castable is prepared according to the following method: the modified zirconium oxide and the modified calcium oxide are added into an organic solvent according to a mass ratio, and a polymerization reaction is carried out by stirring, the suspension is filtered, washed, and dried, and the obtained solid is mixed and stirred evenly with other slag-resistant wear-resistant castable components.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] 1. By reducing the amount of calcium aluminate cement, the problem of large holes caused by dehydration and decomposition of hydrates in the late stage of the castable at high temperature is reduced. At the same time, andalusite will expand slightly under high temperature conditions, further squeezing the cavity structure caused by dehydration, turning large holes into tiny holes, reducing the apparent porosity and improving the compressive and flexural strength;
[0025] 2. Under high temperature conditions, calcium oxide and zirconium oxide will generate high-strength calcium zirconate, which has a melting point of more than 2200°C and can enhance the high temperature resistance and toughness of the material. The common preparation method of calcium zirconate is to use calcium carbonate and zirconium oxide to react under high temperature conditions. Carbon dioxide will be released during the process to make the material have a porous structure. After calcium carbonate is directly added to the casting material, calcium carbonate will decompose into calcium oxide and carbon dioxide at high temperature and disintegrate the whole after solidification, which is not conducive to the stability of the overall structure. By using a modifier to coat calcium oxide with hydrophobicity, not only the problem of calcium oxide and hydration during the pouring process is avoided, but also calcium oxide reacts directly with zirconium oxide, which simultaneously avoids the problem of increased apparent pores leading to reduced strength;
[0026] 3. Calcium oxide and zirconium oxide are coated with silane coupling agent for hydrophobic modification. Compared with other modifiers, the long-chain organic structure of silane coupling agent can play a lubricating role in the process of water preparation of castables, reduce the water consumption of castables, shorten the solidification time, and improve the structural stability at high temperature;
[0027] 4. Adding a large amount of calcium oxide is detrimental to the overall performance of the castable. Calcium zirconate formed by combining with zirconium oxide can reduce this adverse effect. However, it is difficult to mix calcium oxide and zirconium oxide in proportion using traditional mixing equipment, resulting in a large amount of calcium oxide acting at a single site in the castable. Calcium zirconate cannot be generated in large quantities and its function cannot be fully exerted. By polymerizing and cross-linking the mercaptosilane coupling agent and the vinyl silane coupling agent, calcium oxide and zirconium oxide are contacted and combined in proportion and become one, avoiding the uncertainty of contact during mixing and firing, allowing a large amount of calcium zirconate to be generated in situ, giving full play to the excellent characteristics of calcium zirconate in terms of corrosion resistance, impact resistance, wear resistance and high thermal shock stability. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with embodiments, but the protection scope of the technical solution of the present invention is not limited thereto.
[0029] Example 1
[0030] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0031] S1. Preparation of modified calcium oxide: first, the modifier silane coupling agent KH550 (γ-aminopropyltriethoxysilane) and the organic solvent anhydrous ethanol are mixed and stirred at a ratio of 4 mL: 1 L, and then calcium oxide is added at a liquid-solid ratio of 0.02 mL / g of silane coupling agent KH550 to calcium oxide, and the reaction is stirred for 30 minutes. The suspension is filtered and washed with ethanol several times, and the modified calcium oxide is dried at 40°C to obtain a hydrophobic modified calcium oxide powder;
[0032] S2. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 8 parts of andalusite with a particle size of 0-1mm, 5 parts of silicon carbide, 6 parts of modified calcium oxide, 1 part of zirconium oxide, 2 parts of 0-5μm particle alumina, 4 parts of calcium aluminate cement, and 2 parts of sodium tripolyphosphate;
[0033] S3. Put the above components into a mixing drum and stir for 1 hour.
[0034] Example 2
[0035] A slag-resistant and wear-resistant castable, which differs from Example 1 in that the component contents are different: 15 parts of corundum aggregate with a particle size of 0-1 mm, 40 parts of corundum aggregate with a particle size of 1-3 mm, 10 parts of corundum aggregate with a particle size of 3-5 mm, 12 parts of andalusite with a particle size of 0-1 mm, 6 parts of silicon carbide, 8 parts of modified calcium oxide, 1 part of zirconium oxide, 2 parts of 0-5 μm particle aluminum oxide, 6 parts of calcium aluminate cement, and 1 part of sodium hexametaphosphate.
[0036] Example 3
[0037] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0038] S1. Using silane coupling agent kh590 (γ-mercaptopropyltrimethoxysilane) as a modifier and preparing hydrophobic modified calcium oxide according to the method in Example 1;
[0039] S2. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 8 parts of andalusite with a particle size of 0-1mm, 5 parts of silicon carbide, 6 parts of modified calcium oxide, 1 part of zirconium oxide, 2 parts of 0-5μm granular alumina, 1 part of 1-2cm short fiber, 4 parts of calcium aluminate cement, and 2 parts of sodium tripolyphosphate;
[0040] S3. Put the above components into a mixing drum and stir for 1 hour.
[0041] Example 4
[0042] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0043] S1. Using silane coupling agent kh590 (γ-mercaptopropyltrimethoxysilane) as a modifier and preparing hydrophobically modified calcium oxide and hydrophobically modified zirconium oxide according to the method in Example 1;
[0044] S2. Preparation of modified zirconium oxide: first, the silane coupling agent kh590 (γ-mercaptopropyltrimethoxysilane) and the organic solvent anhydrous ethanol were mixed and stirred in a ratio of 4 mL: 1 L, and then zirconium oxide was added at a liquid-solid ratio of 0.04 mL / g of the silane coupling agent kh590 to zirconium oxide, and the reaction was stirred for 30 minutes. The suspension was filtered and washed with ethanol several times, and the modified zirconium oxide was dried at 40 ° C to obtain a hydrophobic modified zirconium oxide powder;
[0045] S3. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 8 parts of 0-1mm andalusite, 5 parts of silicon carbide, 6 parts of modified calcium oxide, 3 parts of modified zirconium oxide, 2 parts of 0-5μm granular alumina, 1 part of 1-2cm short fiber, 4 parts of calcium aluminate cement, and 2 parts of sulfonated naphthalene formaldehyde polymer;
[0046] S4. Put the above components into a mixing drum and stir for 1 hour.
[0047] Example 5
[0048] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0049] S1. Preparation of modified calcium oxide: first, the modifier silane coupling agent kh590 (γ-mercaptopropyltrimethoxysilane) and the organic solvent anhydrous ethanol were mixed and stirred at a ratio of 4 mL: 1 L, and then calcium oxide was added at a liquid-solid ratio of silane coupling agent KH590 to calcium oxide of 0.02 mL / g, and the reaction was stirred for 30 minutes. The suspension was filtered and washed with ethanol several times, and the modified calcium oxide was dried at 40°C to obtain a hydrophobic modified calcium oxide powder;
[0050] S2. Preparation of modified zirconium oxide: first, the modifier silane coupling agent kh570 (γ-methacryloxypropyltrimethoxysilane) and the organic solvent anhydrous ethanol were mixed and stirred in a ratio of 15 mL: 1 L, and then zirconium oxide was added at a liquid-solid ratio of 0.04 mL / g of the silane coupling agent kh570 to zirconium oxide, and the reaction was stirred for 30 minutes. The suspension was filtered and washed with ethanol several times, and the modified zirconium oxide was dried at 40 ° C to obtain a hydrophobic modified zirconium oxide powder;
[0051] S3. The modified calcium oxide and the modified zirconium oxide were put into an organic solvent of anhydrous ethanol, 2% benzoin dimethyl ether catalyst was added and the polymerization reaction was stirred under ultraviolet light for 30 minutes, the suspension was filtered and washed with ethanol several times, and the obtained solid was dried at 40 ° C;
[0052] S4. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 8 parts of andalusite with a particle size of 0-1mm, 5 parts of silicon carbide, 8 parts of modified calcium oxide, 8 parts of modified zirconium oxide, 2 parts of 0-5μm granular alumina, 1 part of short fiber of 1-2cm, 4 parts of calcium aluminate cement, and 2 parts of sodium tripolyphosphate;
[0053] S5. Mix the solid obtained in step S3 with other castable components and stir evenly.
[0054] Comparative Example 1
[0055] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0056] S1. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 5 parts of silicon carbide, 6 parts of modified calcium oxide, 1 part of zirconium oxide, 2 parts of 0-5μm particle alumina, 4 parts of calcium aluminate cement, and 2 parts of sodium tripolyphosphate;
[0057] S3. Put the above components into a mixing drum and stir for 1 hour.
[0058] Comparative Example 2
[0059] A slag-resistant and wear-resistant castable is prepared according to the following method steps:
[0060] S1. Weigh the following components according to the mass ratio: 10 parts of corundum aggregate with a particle size of 0-1mm, 35 parts of corundum aggregate with a particle size of 1-3mm, 5 parts of corundum aggregate with a particle size of 3-5mm, 8 parts of andalusite with a particle size of 0-1mm, 5 parts of silicon carbide, 6 parts of calcium oxide, 1 part of zirconium oxide, 2 parts of alumina with a particle size of 0-5μm, 4 parts of calcium aluminate cement, and 2 parts of sodium tripolyphosphate;
[0061] S3. Put the above components into a mixing drum and stir for 1 hour.
[0062] The castables prepared in Examples 1-5 and Comparative Examples 1-2 were made into test pieces and then heat treated to test their performance. The test results are shown in the following table.
[0063]
[0064]
[0065] According to the above table, the compressive strength and flexural strength of the castables prepared in Examples 1-5 are greatly improved after high-temperature sintering compared with those in Comparative Examples 1-2, and the average abrasion rate effect is only half of that in Comparative Examples 1-2. The prepared slag-resistant and wear-resistant castables have excellent performance compared with traditional castables and are a significant improvement.
[0066] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A slag-resistant and wear-resistant castable, characterized in that: Calculated by weight, the composition includes: 50-65 parts of corundum aggregate, 8-12 parts of andalusite, 5-6 parts of silicon carbide, 6-8 parts of modified calcium oxide, 1-8 parts of zirconium oxide, 2-3 parts of aluminum oxide, 4-6 parts of calcium aluminate cement, and 1-2 parts of water reducing agent.
2. The slag-resistant and wear-resistant castable according to claim 1, characterized in that: The corundum aggregate includes 10-15 parts of a particle size of 0-1mm, 35-40 parts of a particle size of 1-3mm, and 5-10 parts of a particle size of 3-5mm. The andalusite particle size is 0-1mm.
3. The slag-resistant and wear-resistant castable according to claim 1, characterized in that: The aluminum oxide includes 1-2 parts of particles of 0-5 μm and 1-2 parts of short fibers of 1-2 cm.
4. The slag-resistant and wear-resistant castable according to claim 1, characterized in that: The modified calcium oxide is prepared according to the following method: S1. dissolving a silane coupling modifier in an organic solvent; S2. The calcium oxide powder is put into an organic solvent and stirred for 30 minutes; S3. Filter, wash and dry the suspension.
5. The slag-resistant and wear-resistant castable according to claim 1, characterized in that: The zirconium oxide is selected as modified zirconium oxide.
6. The slag-resistant and wear-resistant castable according to claim 5, characterized in that: The modified zirconium oxide is prepared according to the following method: S1. dissolving a silane coupling modifier in an organic solvent; S2. The zirconium oxide powder was added to the organic solvent and stirred for 30 min; S3. Filter, wash and dry the suspension.
7. The slag-resistant and wear-resistant castable according to claim 1, characterized in that: The water reducing agent is one or more of sodium tripolyphosphate, sodium hexametaphosphate, and sulfonated naphthalene formaldehyde polymer.
8. The slag-resistant and wear-resistant castable according to claim 4 or 6, characterized in that: The silane coupling modifier is one of a mercaptosilane coupling modifier, an aminosilane coupling agent, and a vinylsilane coupling agent.
9. A method for preparing a slag-resistant and wear-resistant castable, based on the components in claim 1, characterized in that: Weigh each component according to the ratio and mix them evenly.
10. A method for preparing a slag-resistant and wear-resistant castable, prepared and implemented based on claim 8, characterized in that: The zirconium oxide is modified zirconium oxide, and the slag-resistant wear-resistant castable is prepared according to the following method: the modified zirconium oxide and the modified calcium oxide are added into an organic solvent according to a mass ratio, and a polymerization reaction is carried out by stirring, the suspension is filtered, washed, and dried, and the obtained solid is mixed and stirred evenly with other components of the slag-resistant wear-resistant castable.
Citation Information
Patent Citations
Long-service-life flow stabilizer castable for tundish, flow stabilizer and preparation method of flow stabilizer
CN112358283A
Wear-resistant castable for high-temperature wear part of thermal kiln lining and preparation method of wear-resistant castable
CN117342862A
Pouring material for lime rotary kiln
CN101921128A
Corundum and spinel castable and preparation method thereof
CN102617169A
Preparation method of steel ladle pouring material with slag resistance
CN107382333A